Mouthguard use in youth ice hockey and the risk of concussion: nested case-control study of 315 cases - Chisholm, D. A.; Black, A. M.; Palacios-Derflingher, L.; Eliason, P. H.; Schneider, K. J.; Emery, C. A.; Hagel, B. E. (British Journal of Sports Medicine, 2020)
Background: Concussion is the most common injury in youth ice hockey. Whether mouthguard use lowers the odds of concussion remains an unanswered question.